The Geography of Language Learning: How Region and School Type Shape English Proficiency in Costa Rica - Elizondo-González, Jose Fabián (2026)
This study investigates how high school type (public vs. private) and geographic region (Greater Metropolitan Area [GMA] vs. Non-GMA) intersect to influence English language proficiency outcomes among Costa Rican students. Drawing on national data from 66 886 high school students collected by the Foreign Language Assessment Program (PELEx, for its acronym in Spanish) in 2022, the study aimed to assess whether regional context moderates the relationship between school type and proficiency scores, with a focus on the effectiveness of public bilingual programs. Two moderation models were estimated using multiple regression with robust standard errors. The first model compared typical public and private schools (excluding bilingual types), while the second examined outcomes among public bilingual programs (Experimental Bilingual Schools and Bilingual Groups) relative to private schools. Results showed that public school students in Non-GMA areas were the most disadvantaged, scoring significantly lower than peers in private GMA schools (A2 vs. B2 levels). In contrast, public bilingual programs in GMA regions performed nearly on par with private schools, but their effectiveness declined in Non-GMA areas, where most students reached only B1. These findings demonstrate how regional inequalities compound school-based disparities and highlight the importance of context-sensitive evaluation when interpreting the promise and limitations of bilingual education systems.